Parent’s Expectations Towards Education Management of Preprimary Education Centers of The Namchan Subdistrict Administrative Organization, Seka District, Bungkan Province - ย่อสิทธิสนธิ, วันเพ็ญ (Journal of Graduate MCU KhonKaen Campus, 2015)
The objectives of this research were to study the parents’ expectations, to compare the parents’ expectations, and to study the suggestions towards education management of preprimary education centers of the Namchan sub district administrative organization, Seka district, Bungkan province. The sample were Bankambom preprimary education centers, Bannamchan’s Child development center, and Bandongkapoong’s Child development center for the academic year of 2012 B.E. amount 182 persons by using the frequency, percentages, arithmetic average, and standard deviation. The comparison of parents’ expectations between age and education used the T-Test or independent sample level on .05. analyzing the data with the table of the suggestions. The results of this study showed that, 1. Studying the parents’expectations towards education management of preprimary education centers of the Namchan sub district administrative organization, Seka district, Bungkan province was on the most level namely; the place, building and environment, and safety, the personnel and management, the participation and supporting of academic community and the activity according to the course respectively. 2) The comparison of the parents’ expectations towards education management of preprimary education centers that had the same of age found that it had the independent sample level on .05. 3) The comparison of the parents’ expectations towards education management of preprimary education centers that had the different of age found that it had the independent sample level on .05. The opinions and suggestion about the education’s child development center of Bannamchan, administrative organization, Seka district, Bungkan province were the teachers was sufficient, there should had the driver and cook to support the children, and should had the clean toilets, playground, musical instrument for playing and singing. Letting them known the worship, giving them counted and drawn, giving the parent participate the mother’s day and having the committees of child development center respectively.